Variations in Mid‐ to Late Holocene Nitrogen Supply to Northern Great Barrier Reef Halimeda Macroalgal Bioherms. Issue 2 (12th February 2021) - McNeil, Mardi; Nothdurft, Luke; Erler, Dirk; Hua, Quan; Webster, Jody M.
Abstract: The northern Great Barrier Reef (GBR) Halimeda bioherms have accumulated on the outer continental shelf from calcium carbonate algal sediments over the past ∼10, 000 years and cover >6, 000 km 2 of shelf area. As such, Halimeda bioherms play a key role in the shallow marine carbon cycle over millennial timescales. The main source of nitrogen (N) to these bioherms is thought to be westward transport of upwelled NO3 ‐ ‐rich water from the Coral Sea. However, the primary N source has not been traced geochemically, and we have no understanding of any temporal variation. Here, we reconstruct patterns of N supply to Halimeda bioherms in the GBR since the mid‐Holocene using the 15 N/ 14 N ratio of skeletal‐bound organic N (δ 15 N‐skeletal organic material [SOM]) in modern and fossil Halimeda sediment cores. Average Halimeda skeletal δ 15 N‐SOM was 6.28 ± 0.26‰, consistent with δ 15 N‐NO3 ‐ from western tropical South Pacific (WTSP) thermocline waters. Thus, geochemically validating shelf‐break upwelling of an oceanic N source that regulates bioherm spatial distribution. Halimeda δ 15 N‐SOM decreased by 1‰–2‰ from 5, 000 to 2, 000 cal. yr BP, reaching a minima of 5.5‰ that persisted for almost 1, 000 years. The Halimeda δ 15 N‐SOM variation reflects mid‐ to late Holocene changes in regional climate and intensified El Niño activity that likely facilitated elevated N2 fixation in the WTSP, thereby lowering thermocline δ 15 N‐NO3 ‐ . Thus, Halimeda skeletal material provides a valuable high‐resolution geochemical archive of past oceanographic and climatic processes over centennial to millennial timescales, complementing existing paleoclimate proxy records. Key Points: Well‐preserved fossil Halimeda is a valuable geochemical proxy archive of millennial‐scale oceanographic and climatic processes Nitrogen (N) supply to Halimeda bioherms originates from western tropical South Pacific thermocline waters since at least the past 5, 000 years Halimeda 15 N signature records a 1‰–2‰ change in δ 15 N‐skeletal organic material (SOM) concurrent with regional climate variation and the El Niño Southern Oscillation